IMPLEMENTATION OF CULTURAL POLICY BY STAVROPOL AND KUBAN PARTY AUTHORITIES IN «KHRUSHCHEV THAW» AGE - N. V. Romanova (Гуманитарные и юридические исследования, 2021)
The content of the article is based on archive documents. The main goal is the analysis of primary factors and particular forms of interaction between the power and art culture in Kuban and Stavropol regions in 50-60s of XXth century.